2019
DOI: 10.1063/1.5093549
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise and defects in copper and ruthenium resistors

Abstract: 1.8-MeV proton irradiation to a fluence of 1014/cm2 does not significantly affect the resistance or low-frequency noise of copper or ruthenium resistors fabricated via modern microelectronic fabrication techniques used to form metal lines. The room-temperature noise of these Cu and Ru resistors is surprisingly similar to that of Cu and Pt metal lines and wires fabricated using late-1970s nanofabrication techniques; however, measurements of the temperature dependence of the noise show that the defect kinetics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…One of the examples [1], [15], [67], [72], [73] is shown in Fig. I-10, where defects in graphene transistors activated during irradiation were passivated during high-temperature annealing and were attributed to the influence of hydrogen-and oxygen-related defects.…”
Section: Influence Of Irradiation On 1/f Noisementioning
confidence: 99%
See 2 more Smart Citations
“…One of the examples [1], [15], [67], [72], [73] is shown in Fig. I-10, where defects in graphene transistors activated during irradiation were passivated during high-temperature annealing and were attributed to the influence of hydrogen-and oxygen-related defects.…”
Section: Influence Of Irradiation On 1/f Noisementioning
confidence: 99%
“…In the previous almost 100 years, low-frequency noise with spectral density inversely proportional to frequency ( )S f f  at frequencies f<100 kHz, where α ≈ -1, has been observed and extensively investigated in a variety of microelectronic materials and devices: from metal films, wires and resistors [1] to high-electron-mobility transistors [2], solar cells [3] and graphene devices [4], [5]. It has been found that different physical mechanisms can be responsible for the 1/f noise in different electronic systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that all causes of interferences are removed by proper shielding and positioning of the components, the ultimate sensitivity is set by the intrinsic noise introduced by the DUT bias systems, by the preamplifiers that detect and amplify the noise signal across the DUT and, possibly, by other auxiliary systems such as DUT temperature control systems. While standard instrumentation exists that can be used for laboratory set ups and even wafer level noise testing [47][48][49], depending on the DUT characteristics, dedicated instrumentation may be a better choice in order to maximize sensitivity [50] and, in the specific case of FES applications, portability. The main circuitry solutions will be discussed in section 4.3.…”
Section: Measurement Circuitry Problems: Noise Bandwidthmentioning
confidence: 99%
“…Previously, a new electromigration (EM) test method, based on low-frequency noise (LFN) measurements was proposed [1][2][3] . Contrary to standard test methods, LFN provides non-destructive and faster EM characterization, while enabling a deeper fundamental understanding of EM mechanisms [1][2][3][4][5] . A particularly interesting application of the LFN measurements is the calculation of EM activation energies, based on the model of Dutta et al 6,7 .…”
mentioning
confidence: 99%